(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
With the rapid adoption of mobile learning (m-learning) apps in education, this paper seeks to evaluate their impact on secondary English student learning outcomes. Utilizing a mixed-methods approach, we quantitatively assessed student performance metrics and qualitatively gathered student feedback on their experiences with the apps. The findings reveal both positive and negative impacts of m-learning apps, offering insights for educators, app developers, and policymakers.